Peran Masyarakat Dalam Pencegahan Penyalahgunaan Narkotika - Lalu Saipudin (Fakultas Hukum Universitas Mataram, 2018)
Figures abuse of narcotics in Indonesia is still quite high, so that Indonesia still had to be alert to prevent and combat the abuse and trafficking of illegal narcotics comprehensively and synergy by involving the various elements, both the role of government through institutional functions especially law enforcement agencies, as well as the role of the community as the main shaft within the legal system for the prevention of abuse of narcotics. Based on data from the National Narcotics Agency of West Nusa Tenggara and West Nusa Tenggara Regional Police, West Lombok district, including one of the areas of drug users is high enough in Nusa Tenggara Bara, it is potentially an increase in the prevalence of drug abuse. Community role in the prevention of abuse and trafficking of narcotics reaffirmed in Law No. 35 Year 2009 on Narcotics in Chapter XIII on Community Participation. Optimizing the role of society are also part of the National Narcotics Agency action plan in 2017 as a performance optimization measures in the context of prevention and in order to curb the prevalence of drug abuse. The purpose of this research is to know and analyze the role of society in prevention of narcotics abuse in West Lombok regency, using empirical law research conducted in West Lombok regency, that is research that examine and analyze law effectiveness and law application in relation to society role in prevention of narcotics abuse. The results showed that the role of the community in the prevention of narcotics abuse in West Lombok regency includes: First, the prevention form through education, training or legal counseling is done through cooperation with related institutions or institutions, including National Narcotics Board of West Nusa Tenggara, Social and Cultural Service, Resort Lombok Barat and Non Governmental Organization. Second, strengthening the role of village government is done by active involvement in the prevention of narcotics abusers in the determination of activities and programs, cooperation with law enforcement, and supervision of community activities as part of the development of public order and security. Third, report the narcotics crime to law enforcers, taken by establishing communication with law enforcement that is National Narcotics Board of West Nusa Tenggara and Resort Police of West Lombok.